Erratum to “Nitrifying and heterotrophic population dynamics in biofilm reactors: effects of hydraulic retention time and the presence of organic carbon” - Nogueira, R. (2003)
Erratum to ‘‘Nitrifying and heterotrophic population dynamicsin biofilm reactors: effects of hydraulic retention time and thepresence of organic carbon’’[Water Research 36 (2002) 469–481]. Available at: http://hdl.handle.net/1822/1602